2002
DOI: 10.3354/meps229291
|View full text |Cite
|
Sign up to set email alerts
|

A bioenergetic model for estimating the food requirements of Steller sea lions Eumetopias jubatus in Alaska, USA

Abstract: A generalized bioenergetic model was used to estimate the food requirements of Steller sea lions Eumetopias jubatus in Alaska, USA. Inputs included age-and sex-specific energy requirements by date, population size and composition, and diet composition and energy content. Error in model predictions was calculated using uncertainty in parameter values and Monte Carlo simulation methods. Our model suggests that energy requirements of individuals were generally lowest in the summer breeding season (June to August)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
207
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(217 citation statements)
references
References 89 publications
9
207
0
1
Order By: Relevance
“…Furthermore, there is currently no information on inter-individual variation in the diet of this species, e.g. it is not known whether the observed diet changes are uniform or limited to particular age or sex classes, factors important for determining population responses to environmental variability (Winship et al 2002).…”
Section: Abstract: Australian Fur Seal · Otariid · Stable Isotopes ·mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is currently no information on inter-individual variation in the diet of this species, e.g. it is not known whether the observed diet changes are uniform or limited to particular age or sex classes, factors important for determining population responses to environmental variability (Winship et al 2002).…”
Section: Abstract: Australian Fur Seal · Otariid · Stable Isotopes ·mentioning
confidence: 99%
“…Due to differences in the contributions of various age cohorts to the population (e.g. ages 3 to 9 yr represent > 70% of adult females (Gibbens & Arnould 2009a), such age-related changes may have important implications for estimates of a population's prey consumption (Winship et al 2002).…”
Section: Inter-annual and Inter-individual Variationmentioning
confidence: 99%
“…The threshold of when fishing impacts are insignificant or discountable as well as the level of uncertainty around this threshold is the nexus of the debate. While considerable effort has been expended to understand the seasonal nutritional requirements for individual W-SSLs [22][23][24], less is known about the size of local, seasonal prey populations required to support the recovery of W-SSL populations. For instance, the abundance of pollock, Pacific cod, Atka mackerel, and other prey necessary for central Aleutian Islands W-SSLs during the winter and early spring [25,26] is not simply limited to the fish they consume, but also includes the much larger number of fish necessary in the environment to guarantee successful foraging [27][28][29].…”
Section: Implications For the Aleutian Islands Pollock Fisherymentioning
confidence: 99%
“…More recent work confirms that the population parameters of transients in British Columbia are very similar to those we used. Knowledge of killer whale energetics is sparse (Kriete 1995, Williams et al 2004, Williams & Noren 2009, Noren 2011), but we patterned our approach after those of Moen et al (1997) and Winship et al (2002) with adjustments for the allometric relationship suggested by Williams et al (2004).…”
Section: Introductionmentioning
confidence: 99%